Preschool Education and Inclusion in the North of Chile. The Formation of Young Chileans in the Classrooms of Tarapacá (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
This paper describes the teaching practices of pre-school teachers who play areproductive role of nationalism internalized in children as Chilean citizenships. This happens as the result of a ludic scenario that ritualizes civic and patriotic conduct, through civic commemorations based on the Pacific war, regardless both the cosmopolitan reality and cultural diversity present in classrooms in the Northern part of Chile. Considering this, we propose a new perspective on conducting civic events in early childhood education, to make them more inclusive and consistent with the cultural reality of the region of Tarapacá, Chile's most multicultural region.
Keywords: Preschool education; Tarapacá; Nationalism; Inclusion; Pacific War; Civic Acts